Building safety cultures at the frontline: An emancipatory Practice Development approach for strengthening nursing surveillance on an acute care ward. Issue 5 (16th June 2021) - Peet, Jacqueline; Theobald, Karen A.; Douglas, Clint
Abstract: Aim: To evaluate an emancipatory Practice Development approach for strengthening nursing surveillance on a single medical‐surgical ward. Background: Registered nurses keep patients safe in acute care settings through the complex process of nursing surveillance. Our interest was understanding how frontline teams can build safety cultures that enable proactive nursing surveillance in acute care wards. Design: A year‐long emancipatory Practice Development project. Methods: A collaborative relationship was established around a shared interest of nursing surveillance capacity and researcher embedded on a medical‐surgical ward. Critical analysis of workplace observations and reflection with staff generated key sites for collective action. Ward engagement was supported by creative Practice Development methods including holistic facilitation, critical reflection and action learning. An action learning set was established with a group of clinical nurses, facilitating practitioner‐led change initiatives which strengthened nursing surveillance and workplace learning. Evaluation supported an iterative approach, building on what worked in an acute care context. Immersive researcher evaluation, drawing on multiple data sources, generated an analysis of how ward nursing surveillance capacity can be strengthened. COREQ criteria guided reporting. Results: The ward moved through a turbulent and transformative process of resistance and retreat towards a new learning culture where nursing surveillance was visible and valued. Staff developed and sustained innovations including the 'My MET Call series', a 'Shared GCS initiative', an enhanced 'Team Safety Huddle', and staff‐led Practice Development workshops. These new practices affirmed nurses' agency, asserted nurses' clinical knowledge, positioned nurses to participate in team decision‐making and humanised care. Conclusion: Working collaboratively with frontline staff enabled bottom‐up sustainable innovation to strengthen nursing surveillance capacity where it mattered most, at the point of care. Relevance to clinical practice: Emancipatory Practice Development enables the profound impact of small‐scale, microsystem level practice transformation. It is an accessible methodology for clinical teams to develop effective workplace cultures.